Cum se face ex :11•11-{11-[2x-(x:2+56):10]:10}:10=120
Răspunsuri la întrebare
Răspuns de
0
11•11-{11-[2x-(x:2+56):10]:10}:10=120
121-{11-[2x-(x:2+56):10]:10}=120-121
-{11-[2x-(x:2+56):10]:=-1×10
11-[2x-(x:2+56):10]:10=10
-[2x-(x:2+56):10]=10-11
-[2x-(x:2+56):10]=-1
2x-(x:2+56)=1×10
2x-x/2=10+56
3x/2=66
x=66×2/3=44
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă
Istorie,
10 ani în urmă